Acoso callejero de las estudiantes de la UTMACH y la intervención del trabajo social desde la perspectiva feminista, 2021 - 2022 - Guerrero Carrión, Alejandra Elizabeth (Machala: Universidad Técnica de Machala, 2022)
The present research work seeks to make street harassment visible as a form of sexual violence that threatens the physical, psychological and moral integrity of many women around the world and that must be denatured, since said normalization is present in society due to the lack of education that exists on the subject and the cultural and social constructions that support it. This problem directly affects women, and although it is true that men also suffer from street harassment, those situations do not occur to a large extent as it happens with the aforementioned ones. Returning to the idea of making street harassment visible, the idea of associating it with sexual violence is proposed, since in addition to being a problem that generates negative repercussions due to the unwanted behavior of a sexual nature that the victims receive, the aggressors through they manifest the oppression and domination they have over women. From this point of view, through the bibliographic review, it is intended to describe the evolution of street harassment, from gallantry and compliments to physical, verbal and psychological aggression, which from a macho and patriarchal perspective seeks to dominate and lower women and exclude them from the freedom to travel public spaces without fear. Likewise, the intervention of the social worker from the feminist perspective is included to explain why these professionals are agents of change who struggle to provide tools that allow mitigating the aforementioned problem, and in turn how the feminist vision helps to provide clarity to the problems that directly affect women and contribute to existing inequality gaps. Feminist groups are integrated in a way that seeks to make society aware of the patriarchal and heteronormative ideals that generate disputes about harassment as a form of violence. The social worker, through intervention, seeks to reduce the inequality gaps that exist in society and bases his profession on achieving true gender equality where women can develop equally, expressing opinions freely and enjoying their rights. rights fully, since when naming feminism reference is made to the struggle led by the collective, for a world in which the only difference that exists between the sexes is to differentiate them but not to separate them, that is to say suppress social structures that seek to exclude women. It is due to the aforementioned that the main objective of the research is to be able to mitigate the negative effects that street harassment entails in the comprehensive development of UTMACH students in the period 2021-2022, through the design of an intervention plan. , which in addition to defining the causes for which such harassment occurs, also presents the effects that are generated in the victims. The theoretical framework is based on articles which have been found in scientific databases, thus serving to complement the research through the analysis of their ideas, in addition, the use of a simple random sampling is proposed to obtain the results of the investigation.
El presente trabajo de investigación busca visibilizar el acoso callejero como una forma de violencia sexual que atenta contra la integridad física, psicológica y moral de muchas mujeres alrededor del mundo y que debe ser desnaturalizado, pues dicha normalización se ve presente en la sociedad debido a la falta de educación que existe sobre el tema y por las construcciones culturales y sociales que la respaldan. Dicha problemática afecta directamente a las mujeres, y aunque es verdad que los hombres también sufren de acoso callejero, aquellas situaciones no se dan en gran medida como sucede con las antes mencionadas. Retomando la idea del visibilizar el acoso callejero se plantea la idea de asociar el mismo con la violencia sexual, pues además de ser una problemática que genera repercusiones negativas debido a las conductas no deseadas de tipo sexual que reciben las víctimas, los agresores a través de las mismas manifiestan la opresión y dominación que tienen sobre las mujeres. Desde esta óptica se pretende a través de la revisión bibliográfica describir la evolución del acoso callejero, desde la galantería y los piropos hasta la agresión física, verbal y psicológica, que desde una perspectiva machista y patriarcal busca dominar y rebajar a la mujer y excluirla de la libertad de transitar espacios públicos sin temor. Así mismo, se incluye la intervención del trabajador social desde la perspectiva feminista para explicar el por qué dichos profesionales son agentes de cambio que luchan por brindar herramientas que permitan mitigar la problemática antes mencionada, y a su vez como la visión feminista ayuda a brindar claridad a los problemas que afectan directamente a la mujer y que contribuyen a las brechas de desigualdad que existen. Los colectivos feministas se integran de forma que buscan concientizar a la sociedad sobre los ideales patriarcales y heteronormativos que generan disputas sobre el acoso como una forma de violencia. Es debido a lo mencionado anteriormente que la investigación tiene por objetivo principal el mitigar los efectos negativos que conlleva el acoso callejero en el desarrollo integral de las estudiantes de la UTMACH en el periodo 2021-2022, a través del diseño de un plan de intervención, que además que definir las causas por las cuales se da dicho acoso también presenta los efectos que se generan en las víctimas. El marco teórico se encuentra fundamentado por artículos los cuales se han encontrado en bases de datos científicas sirviendo así para complementar la investigación a través del análisis de las ideas de los mismos, además se plantea la utilización de un muestreo aleatorio simple para obtener los resultados de la investigación.
Keywords: ACOSO CALLEJERO; VIOLENCIA SEXUAL; TRABAJO SOCIAL; FEMINISMO